2018
DOI: 10.1007/s00439-018-1942-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies for corneal and refractive astigmatism in UK Biobank demonstrate a shared role for myopia susceptibility loci

Abstract: Previous studies have suggested that naturally occurring genetic variation contributes to the risk of astigmatism. The purpose of this investigation was to identify genetic markers associated with corneal and refractive astigmatism in a large-scale European ancestry cohort (UK Biobank) who underwent keratometry and autorefraction at an assessment centre. Genome-wide association studies for corneal and refractive astigmatism were performed in individuals of European ancestry (N = 86,335 and 88,005 respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 75 publications
(108 reference statements)
2
40
2
Order By: Relevance
“…288 289 Corneal astigmatism and age 290 Corneal astigmatism decreases significantly with age by an average 0.06D in both eyes per decade even 291 after controlling for weight and height (Table 3.2). This is contrary to what is reported by [34] namely 292 that the level of corneal astigmatism is relatively constant across age. As reported by Shah et al in a 293 previous UKBB analysis [34], we did confirm the stronger association between age and refractive 294 (cylindrical) astigmatism in right eye (B=0.011 (0.010 to 0.011), P<.001) and left eye (B=0.010 (0.09 to 295 0.010), P<0.001) ( Figure S3.a).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…288 289 Corneal astigmatism and age 290 Corneal astigmatism decreases significantly with age by an average 0.06D in both eyes per decade even 291 after controlling for weight and height (Table 3.2). This is contrary to what is reported by [34] namely 292 that the level of corneal astigmatism is relatively constant across age. As reported by Shah et al in a 293 previous UKBB analysis [34], we did confirm the stronger association between age and refractive 294 (cylindrical) astigmatism in right eye (B=0.011 (0.010 to 0.011), P<.001) and left eye (B=0.010 (0.09 to 295 0.010), P<0.001) ( Figure S3.a).…”
contrasting
confidence: 99%
“…This is contrary to what is reported by [34] namely 292 that the level of corneal astigmatism is relatively constant across age. As reported by Shah et al in a 293 previous UKBB analysis [34], we did confirm the stronger association between age and refractive 294 (cylindrical) astigmatism in right eye (B=0.011 (0.010 to 0.011), P<.001) and left eye (B=0.010 (0.09 to 295 0.010), P<0.001) ( Figure S3.a). The fact that refractive astigmatism increases with age but that corneal 296 astigmatism decreases with age suggest that lenticular astigmatism may be driving the increase in 297 refractive astigmatism, possibly due to the onset of presbyopia.…”
contrasting
confidence: 99%
“…The online version of this article (https ://doi.org/10.1007/s0043 8-020-01666 -w) contains supplementary material, which is available to authorized users. h SNP 2 = 0.35-0.39% (Guggenheim et al 2015;Shah et al 2018). Genome-wide association studies (GWAS) have identified approximately 150 genetic variants associated with refractive error, which together explain approximately 4-6% of the inter-individual variation (Kiefer et al 2013;Verhoeven et al 2013;Tedja et al 2018).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…To identify genes associated with the development of refractive errors in humans among the genes whose expression correlated with refractive eye development in mice, human homologs of candidate mouse genes were examined for association with refractive error in the international genome-wide association study (GWAS) of refractive error carried out by the Consortium for Refractive Error and Myopia (CREAM) [54] and the UK Biobank Eye and Vision consortium sample [71] using the Multi-marker Analysis of GenoMic Annotation (MAGMA) [72]. Human homologs of candidate mouse genes were obtained from Ensembl BioMart and were mapped according to gene definitions in the NCBI Entrez Gene database.…”
Section: Identification Of Genes Associated With Refractive Error In mentioning
confidence: 99%